High directional aerosol fluorescence distribution affected by Mie scattering during femtosecond laser filamentation in air. (June 2023) - Xue, Jiayun; Zeng, Xi; Guo, Lanjun; Guo, Rui; Zhang, Zhi; Chu, Chunyue; Cheng, Zhenzhou; Zhang, Nan; Lin, Lie; Liu, Weiwei
Highlights: Filament-induced aerosol fluorescence emission appears a strong angular dependence. The backward angular distribution of the aerosol fluorescence can be attributed to Mie scattering. The divergence angle of aerosol fluorescence radiation is affected by the particle size distribution. Abstract: Backward angular distributions of the sodium fluorescence in NaCl aerosols induced by femtosecond laser filamentation in air with a distance of 10 m are measured. The recorded signals appear as strong angular dependence. Further study indicates that it could be associated with the Mie scattering of the filamentation-induced "aerosol lasing" in the forward direction. These results will benefit the remote-sensing of air pollutants by femtosecond laser filamentation-based LIDAR (light detection and ranging).